Organizational culture and its influence on knowledge management best practices in Colombian SMEs (2016)
The goal of this paper is to present the relationship between organizational culture and knowledge management best practices for SMEs in Colombia, which is part of an evaluation model of knowledge management that was applied to 321 companies. For this purpose, we used analysis and synthesis methods as well as a type of exploratory and correlational descriptive study. The conclusion was that culture moderates significantly and positively good knowledge management practices. This study is expected to contribute to the development of small and medium enterprises in the country to help them formulate actions that enhance their growth